SIRT1 Is the Target Gene for 2,3,5,4’-Tetrahydroxystilbene-2-O-β-D-Glucoside Alleviating the HUVEC Senescence - Guo, Yan; Fan, Wenxue; Xie, Yuefeng; Cao, Shuyu; Wan, Haitong; Jin, Bo (Frontiers in Pharmacology, 2020)
This study aimed to explore the effects of 2,3,5,4'-tetrahydroxy-stilbene-2-O-β-d-glucoside (TSG) on the senescence of human umbilical vein cells (HUVECs) induced by hydrogen peroxide (H2O2) and to identify the potential targets mediating its protective action. HUVEC cells pre-treated with TSG for 24h were exposed to H2O2 treatment. TSG significantly decreased H2O2-induced cellular senescence, as indicated by reduced senescence-associated β-galactosidase (SA-β-gal) positive staining, the proportion of cells in the G1 phase, cell apoptosis, p21, and plasminogen activator inhibitor-1 (PAI-1) expression. Moreover, TSG promoted SIRT1 expression. When SIRT1 was inhibited by EX527 or SIRT1 siRNA, the anti-aging effect of TSG is diminished according to the increased proportion of cells in the G1 phase, cell apoptosis, p21, and PAI-1 expression. Overall, our study established TSG as an anti-senescence compound that exerts its protective action by regulating SIRT1 expression.